2013
DOI: 10.1590/s2179-975x2013000400010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of local and landscape characteristics on the distribution and diversity of fish assemblages of streams in the Ivinhema River basin, Upper Paraná River

Abstract: OBJECTIVES: Among the most relevant issues in community ecology is the influence of different ways of addressing the pattern of diversity and distribution of species, and based on this, the present study sought to evaluate the influence of landscape and local characteristics on the richness and composition of fish assemblages in the Ivinhema River basin. METHOD: In the present study, we used data of distribution of fish species in 25 stretches of streams of the Ivinhema River basin, Upper Paraná River, aiming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
(54 reference statements)
0
2
0
3
Order By: Relevance
“…The results showed that local environmental variables are more important than landscape variables in structuring fish assemblages in the Cerrado streams studied. have less explanatory power than local factors (Johnson, Furse, Hering & Sandin, 2007;Lammert & Allan, 1999;Lemke & Súarez, 2013). However, the relative importance of local and landscape factors may depend on the spatial scale investigated (Junqueira et al, 2016).…”
Section: Relative Importance Of Local and Landscape Environmental Vmentioning
confidence: 99%
“…The results showed that local environmental variables are more important than landscape variables in structuring fish assemblages in the Cerrado streams studied. have less explanatory power than local factors (Johnson, Furse, Hering & Sandin, 2007;Lammert & Allan, 1999;Lemke & Súarez, 2013). However, the relative importance of local and landscape factors may depend on the spatial scale investigated (Junqueira et al, 2016).…”
Section: Relative Importance Of Local and Landscape Environmental Vmentioning
confidence: 99%
“…As comunidades de peixes de igarapés possuem forte relação com as variáveis físicas e químicas e as características geoambientais (MENDONÇA et al, 2005) e suas alterações podem indicar poluição dos ecossistemas aquáticos (TOLEDO et al, 2002). As características dos corpos d'água amazônicos são de difícil classificação segundo o que é estabelecido pela Resolução CONAMA n°357/2005 que trata da classificação e enquadramento de corpos d'água, bem como as condições e padrões de lançamentos de efluentes, pois suas características são especificas e variam de acordo com o ambiente e processos geoquímicos da região e pluviosidade (LEMKE et al, 2013). Para serem consideradas ambientes poluídos ou alterados estes corpos d'água precisam ter características perceptíveis na visão ou olfato (SILVA et al, 2013).…”
Section: Discussionunclassified
“…O estudo de Anjos ( 2005) descreve que as famílias Characidae, Lebiasinidae são sempre representativas nas categorias dos insetos alóctones, o que foi corroborado no presente estudo. Diversos estudos avaliam que estes sistemas alóctones possuem significativa relação com os efeitos abióticos dos igarapés (MENDONÇA et al, 2005;ESPIRITO-SANTO et al, 2009;LEMKE et al, 2013). Os dados do presente estudo não nos permitem inferir que viveiros de criações de peixes no leito do riacho estejam promovendo mudanças tróficas nas comunidades de peixes nos igarapés estudados.…”
Section: Discussionunclassified
“…Embora os efeitos da predação tenham sido bem registrados em outros ambientes (Latini & Petrere Jr. 2004, Pelicice & Agostinho 2009, nos riachos as evidências ainda são escassas. Por exemplo, existem indícios de que o bagre-africano Clarias gariepinus (Siluriformes, Clariidae) está afetando negativamente populações nativas em riachos na bacia do rio Ivinhema, Alto rio Paraná, estado do Mato Grosso do Sul (Lemke & Súarez 2013). Da mesma forma, a presença do tucunaré Cichla cf.…”
Section: Predaçãounclassified